Expected Time to Recruitment in an Organization with Two Grades using a Univariate Recruitment Policy Involving Two Thresholds - 2V . Vasudevan, 1A. Srinivasan* and (Recent Research in Science and Technology, 2011)
An organization with two grades subjected to loss of man power due to the policy decisions taken by the organization is considered in this paper. Two mathematical models are constructed and an appropriate univariate recruitment policy, based on shock model approach involving optional and mandatory thresholds for the loss of manhours in each grade is suggested. Performance measures namely mean and variance of the time to recruitment are obtained for both the models when (i) the loss of manhours process forms a sequence of independent and identically distributed exponential random variables (ii) the inter-decision times are independent and identically distributed exponential random variables and (iii) the optional thresholds are exponential random variable and the distributions of the mandatory thresholds have SCBZ property. The analytical results are substantiated by numerical illustrations and the influence of nodal parameters on the performance measures is also analyzed.